2014
DOI: 10.1096/fj.14-255364
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein‐energy malnutrition during early pregnancy in sheep impacts the fetal ornithine cycle to reduce fetal kidney microvascular development

Abstract: This paper identifies a common nutritional pathway relating maternal through to fetal protein-energy malnutrition (PEM) and compromised fetal kidney development. Thirty-one twin-bearing sheep were fed either a control (n=15) or low-protein diet (n=16, 17 vs. 8.7 g crude protein/MJ metabolizable energy) from d 0 to 65 gestation (term, ∼145 d). Effects on the maternal and fetal nutritional environment were characterized by sampling blood and amniotic fluid. Kidney development was characterized by histology, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…The formation of vascular tissue is regulated by various angiogenic factors. In animal models of programming, numbers of microvascular blood vessels were decreased in various vascular beds from fetal sheep and rats (57, 107,275,308,342). Furthermore, blood from umbilical cords of IUGR pregnancies (385) and capillaries in IUGR rats (308) have both been shown to have a reduced angiogenic capacity.…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…The formation of vascular tissue is regulated by various angiogenic factors. In animal models of programming, numbers of microvascular blood vessels were decreased in various vascular beds from fetal sheep and rats (57, 107,275,308,342). Furthermore, blood from umbilical cords of IUGR pregnancies (385) and capillaries in IUGR rats (308) have both been shown to have a reduced angiogenic capacity.…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…39 Prior research in a sheep model showed that maternal protein restriction reduced ornithine in fetal plasma and amniotic fluid. 40 The higher maternal ornithine levels seen in our study may reflect impaired transport by the placenta, resulting in decreased fetal ornithine and thus impaired growth potential due to limited polyamines. Alternatively, FGR may precede altered ornithine uptake through a yet undefined mechanism.…”
Section: Discussionmentioning
confidence: 63%
“…Not only was this condition comparable to humans, but also showed that the scanning method was well tolerated by the animals and that the technique itself was comparable to human studies [74]. In addition to the use of tracers and air to differentiate vasculature, a number of researchers have used corrosions casting in order to understand vascularisation in a number of disorders and systems, ranging from kidney development to ocular disorders in species from mice through to sheep [75][76][77]. Computed Tomography -Advanced Applications…”
Section: Clinical and Research Investigations Into Vasculaturementioning
confidence: 88%